Modelling and predicting high-rise dwellings costs in Singapore - Chua, Beng Hwa. (2009)
The public housing in Singapore (commonly known as the HDB flats) accommodates about 87% of the population in Singapore. Due to the current competitive construction market, the common estimating methods adopted for the Lump Sum Contract without Bills of Quantities have imposed more risks on tenderers. Many research studies have been based on the principle of cost significance, which hypothesizes that a relatively small number of cost-significant items (about 20% of the total number of items) contributes to a large proportion (about 80%) of the total cost.